PERBANDINGAN PERFORMANS BROILER YANG DIBERI KUNYIT DAN TEMULAWAK MELALUI AIR MINUM - Tantalo, Syahrio (Jurnal Penelitian Pertanian Terapan, 2011)
The objective of the research was to know comparation of broiler performance when water kunyit and temulawak of consumption. Level of water kunyit and temulawak as treatment was 10 g/600 ml. Broiler that used was Lohmann unsexed. Numbers of treated chicken were 200 Day Old Chicken (DOC) Lohmann unsexed that from PT. Multi Breeder Adirama Indonesia (MBAI). Experiment was designed with two treatments of broiler performance when water kunyit and temulawak of consumption and each treatment had 15 replications. Each replication was 6 or 7 DOC. To compare the of broiler performance that effect two of treatments, data was analyzed using t-student on signification 5% (Steel dan Torrie, 1993). Parameters measured were water consumption, feed intake, weight gain, feed conversion, and income over feed cost. Results showed there were broiler performance on water consumption that temulawak of consumption significant (P<0,05) of highest then water kunyit consumption, but no significant effect on feed intake, and body weight gain, feed conversion, and income over feed cost. Keywords: water kunyit, performance, strain, broiler